2022
DOI: 10.1037/vio0000405
|View full text |Cite
|
Sign up to set email alerts
|

Peer factors as mediators of relations between exposure to violence and physical aggression in middle school students in a low-income urban community.

Abstract: Objective: Although prior research has demonstrated that peers influence both physical aggression and exposure to violence during adolescence, few studies have investigated the extent to which peers play a role in relations between physical aggression and violence exposure. This longitudinal study examined peer pressure for fighting, friends' delinquent behavior, and friends' support for fighting as mediators of relations between exposure to violence through witnessing and victimization, and adolescents' frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This study focused on perceived parental messages. However, there are other factors within adolescents' lives, such as community and peer factors (Farrell, Pittman, Bettencourt, et al, 2022; Farrell, Pittman, O'Connor, et al, 2022; both based on longitudinal data from the current data set), that may impact their beliefs, which may then influence their behaviors. Although effect size estimates were small in this study, this is common in longitudinal studies when variables have high stability and concurrent cross‐variable correlations (Adachi & Willoughby, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study focused on perceived parental messages. However, there are other factors within adolescents' lives, such as community and peer factors (Farrell, Pittman, Bettencourt, et al, 2022; Farrell, Pittman, O'Connor, et al, 2022; both based on longitudinal data from the current data set), that may impact their beliefs, which may then influence their behaviors. Although effect size estimates were small in this study, this is common in longitudinal studies when variables have high stability and concurrent cross‐variable correlations (Adachi & Willoughby, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An additional dimension supported in prior research (Farrell et al, 2019) is the belief that fighting is sometimes unavoidable. Studies have found that beliefs against fighting and beliefs supporting aggression predict changes in aggression (e.g., Farrell, Pittman, O'Connor et al, 2022, based on longitudinal data from the current data set; McMahon et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This manuscript was based on data from an 8-year project that collected longitudinal data within each school year from 10 cohorts of students attending three urban middle schools. Several prior manuscripts based on these data have examined bidirectional relations between exposure to violence and physical aggression (Farrell, Thompson, Curran, & Sullivan, 2020), peer factors as mediators (Farrell, Pittman, O'Connor, & Sullivan, 2022), and moderators (Coleman & Farrell, 2021) of relations between violence exposure and physical aggression, and beliefs as mediators of relations between violence exposure and physical aggression (Farrell, Pittman, Bettencourt, et al, 2022).…”
Section: Ac K Now L E D G M E N T Smentioning
confidence: 99%